Digitalising the Clearance Processes of Higher Education Institutions through the Design and Implementation of an Online Clearance System (International Journal of Scientific Research and Management (IJSRM), 2023)
Students in Higher Education Institutions (HEIs) are expected to participate in a number of important activities throughout their time in school including clearance before graduation. Clearance serves as a means of ensuring graduating students satisfy all required administrative criteria. Both students and clearing officers face a daunting task as a result of the present manual clearance procedures in most HEIs. The development of this online student’s clearance system (UEW-SOCS) was done using the agile methodology. The languages and technologies used are ASP.NET MVC 5, MSSQL 2014 and JavaScript, HTML and CSS. The result is an effective and efficient web-based application that overcomes the challenges of manual paper-based systems characterized by mundane tasks by providing a responsive interface with role-based access to ensure high security. Ultimately, this study designed and implemented a successful and effective online clearance system for Higher Education Institutions that could be a critical decision support system.